Physicochemical, textural, and sensory properties of wheat-based crackers substituted with tilapia (Oreochromis niloticus) and green seaweed (Ulva lactuca) flours - Nani Ratnaningsih; Badraningsih Lastariwati; Arum Widyastuti Perdani (jurnal1, 2026)
Crackers are a popular snack made from wheat flour that is low in protein and minerals. Tilapia (Oreochromis niloticus) and green seaweeds, such as Ulva lactuca, contain high protein and minerals that can prevent nutritional deficiencies in children; however, their application in bakery products remains a challenge. The objective of research was to evaluate the physicochemical, texture, and sensory characteristics of wheat-based crackers (F0) with the substitution of 25% tilapia flour (F1) and the addition of 1-3% Ulva lactuca flour (F2, F3, F4). Protein and iron content of tilapia crackers (F1) were increased by 98% and 18%, respectively, compared to F0. Furthermore, adding Ulva lactuca flour to tilapia crackers enhanced protein and iron content by 111-122 % and 63-89 %, respectively, compared to F0. Substitution of tilapia and Ulva lactuca flours also increased the browning index, cohesiveness, adhesiveness, crispiness, and resilience but decreased the lightness (L*), a*, and b*, hardness, and crunchiness of crackers. However, the higher addition of Ulva lactuca decreased the physicochemical, color, texture properties, and sensory acceptance. Tilapia crackers with the addition of 1% Ulva lactuca contain 23.06 ± 0.05 g/100 g of protein and 7.57 ± 0.27 mg/100 g of iron and are more preferred than other formulations, suggesting a high in protein and iron snack for children.